Diagnostic role of hysteroscopy in abnormal uterine bleeding: a comparative study of hysteroscopy findings with histopathology from Mysore, South India - Shivanagappa, Mamatha; Veerabhadrappa, Vinutha K.; Mahesh, Madhumitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Dilatation and curettage has long been the diagnostic gold standard for abnormal uterine bleeding. However, even a trained gynecological curettes at best 70-80% of the endometrium. Hysteroscopy is gaining acceptability over other diagnostic technique like dilatation and curettage, hysterosalpingogram and ultrasound. The objective of this study is to find out the role of hysteroscopy in abnormal uterine bleeding and to compare hysteroscopy findings with histopathology. Methods: Fifty patients in perimenopausal age group with abnormal uterine bleeding attending JSS Medical College and Hospital Mysore, during the period 1999-2001 were studied by diagnostic hysteroscopy followed by dilatation and curettage. Results: Mean age of the study group was 44.3% years (±2.5 SD). Menorrhagia was the commonest symptom and was found in 68% of the patients. Diagnostic hysteroscopy identified 23 cases as Normal endometrium, 16 cases as endometrial hyperplasia, 3 cases as atrophic endometrium, 4 cases as endometrial polyp, 4 cases as fibroids. Compared with histopathological findings as definitive diagnosis, hysteroscopy correctly picked up 19 cases of (86.9%), normal endometrium, 12 cases of hyperplasia (75%), 3 cases of atrophic endometrium (100%), 4 cases of polyps (100%), and 4 cases of fibroid (100%). Conclusions: Hysteroscopy should be considered as a basic and essential diagnostic procedure in the diagnostic work up of abnormal uterine bleeding.